A needs analysis of the assessed writing genres of a 1st year undergraduate engineering programme. - Ketteringham, Matthew (2015)
Increasing numbers of non-native English speakers (NNES) are studying at English-medium universities. This increase of students has stimulated the need for EAP instruction, so students can become competent in the discourse conventions of their chosen academic community. The purpose of this research was to carry out a needs analysis (NA) of a 1st year Engineering programme at an English-medium university. A case study approach was used to gain a deeper understanding of the writing requirements of 1st year Engineers and to influence teaching and learning within the School of Engineering (SOE). The methodology used to carry out the NA included genre analysis of institutional artefacts, and interviews and focus groups with faculty and students. The results of the genre analysis highlighted nine writing genres for assessed coursework and three genre families used for examinations. The results of faculty interviews and student focus groups found the importance of English varied across the discipline, but communication was seen as very important for Engineers. Also, students had experience and understanding of the majority of genres; however, difficulties in writing arose through a lack of instruction and feedback. Therefore, a need for in-sessional writing support is suggested to improve student writing at the SOE. This case study has highlighted a further need for research of student writing across all four years within the SOE.